DNA damage repair genes expression in population exposed to persistent organic pollutants - He, Xiaobo; Jing, Yaqing; Li, Keqiu; Zhao, Yuxia; Yang, Caihong; Qiaoyun Yang; Xinghua Qiu; Li, Guang (Journal of Environment and Health, 2014)
Objective To explore the relationship between persistent organic pollutants exposure and DNA damage repair in the residents in electronic waste disposing area (e-waste area). Methods Peripheral blood persistent organic pollutants contents of the residents (n=23) in e-waste area and control area(n=25) were determined in a region of north China. The expression of 126 genes of DNA damage repair pathway in the blood samples of two groups was determined by RNA-seq in November, 2011. Results Various POPs showed significantly higher concentration in the exposed group than those in non-exposed group. A total of 17 genes showed differential expression,four (NEIL3, EXO1,MA PK12 and TP73) of which showed significant differential expression between the two groups. A total of nine genes were up-regulated and eight genes were down -regulated among 17 differential expression genes. Interestingly,the expression of certain genes,i.e., MA PK12, EXO1, NTHL1, GADD45G, RA D51, RAD51B appeared to be more significantly different merely among the females of the exposed and non-exposed group,while the expression of RA D54L, DMC1, BBC3, UNG, XRCC6BP1, TP73 merely occurred differential among the males. Conclusion POPs contents in peripheral blood of residents in e -waste area increased significantly, DNA damage repair -related genes expression condition has changed. The differential expression of genes in DNA damage repair system participates in various DNA damage repair pathway and has an effect on it. Gender difference may exist in response to POPs-mediated DNA damage.目的了解电子垃圾处理区域人群中持久性有机污染物(POPs)暴露与DNA损伤修复的关系。方法于2011年11月,检测某电子垃圾处理区域居民(暴露组 ,n=23)及非暴露地区居民(非暴露组,n=25)外周血POPs含量。以RNA测序比较两组血样中DNA损伤修复通路中126个基因的表达情况。结果 暴露组人群外周血多氯联苯(PCBs)、多溴联苯醚(BDEs)、得克隆(DP)的含量高于非暴露组;17个基因出现差异表达,其中NEIL3、EXO1 、MAPK12、TP73表达出现统计学差异。17个差异表达基因中9个基因下调,8个基因上调。MAPK12、EXO1、NTHL1、GADD45G、 RAD51、RAD51B仅在女性暴露组和非暴露组间出现差异;而RAD54L、DMC1、BBC3、UNG、XRCC6BP1、TP73仅在男性出现差 异表达。结论本次调查的电子垃圾处理区域人群外周血POPs含量高于非暴露组,DNA损伤修复相关基因表达量存在一定差异。机体对POPs所致DNA损伤 的应答机制可能存在性别差异。